Pengaruh corporate governance dan kualitas audit terhadap kinerja keuangan pada perusahaan LQ45 yang terdaftar di bursa efek Indonesia - Meidona, Syofria; Yanti, Rima (Jurnal Indovisi, 2018)
The principle of a consistent Corporate Governance will preclude the possibility of engineering performance which resulted in the value of the company's fundamentals are not reflected in the financial statements. Quality audit is very important because of the high quality of audit will produce reliable financial reports as the basis for decision making.This research was conducted at company of LQ45 company which listed in Bursa Efek Indonesia. The purpose of this study is to test partially and simultaneously the influence of corporate governance and audit quality on financial performance at LQ45 company listed in Indonesia Stock Exchange year 2011-2016. This type of research is quantitative research. The object of this study is the banking sector companies in LQ45 companies listed on the Indonesia Stock Exchange in 2011-2016. Data analysis method used is descriptive analysis and multiple regression with the help of IBM SPSS Statistic 23 License Authorization Wizard.Based on statistical calculations with SPSS, it can be seen the results of partial test of corporate governance has no significant effect on financial performance because the value of beta coefficient = 0,014 greater than the required level of significance is 0,071> 0,05. And audit quality have positive significant effect to financial performance because beta coefficient value = -0,010 is smaller than required level of significance that is 0,007 < 0,05. Meanwhile, if simultaneously tested corporate governance and audit quality have a significant positive impact on financial performance because the value of ANOVA Sig = 0,022 is smaller than required level of significance that is 0,022 <0,05.